2018
DOI: 10.1002/jum.14910
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐Care Ultrasonography (POCUS) in a Community Emergency Department: An Analysis of Decision Making and Cost Savings Associated With POCUS

Abstract: Objectives Point‐of‐care ultrasonography (POCUS) is an increasingly integral part of emergency medicine. This study investigated community emergency department physicians’ choices regarding ultrasonography as a branch point in clinical decision making. Methods During shifts covering all days of the week and all time‐spans over a 3‐month period, emergency department physicians were interviewed whenever POCUS was used. Questions focused on the role of POCUS in clinical management and on tests avoided because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 31 publications
0
48
0
1
Order By: Relevance
“…Finally, we identified a collection of studies evaluating the downstream impact of emergency US on resource utilization [48][49][50][51][52]. One study found that patients who had POCUS as opposed to radiology scans were at increased risk of having further confirmatory studies ordered compared to those who had the initial US done by radiology [50].…”
Section: Miscellaneous Studiesmentioning
confidence: 99%
“…Finally, we identified a collection of studies evaluating the downstream impact of emergency US on resource utilization [48][49][50][51][52]. One study found that patients who had POCUS as opposed to radiology scans were at increased risk of having further confirmatory studies ordered compared to those who had the initial US done by radiology [50].…”
Section: Miscellaneous Studiesmentioning
confidence: 99%
“…Although ultrasound has been integrated well into undergraduate medical education in the USA, this cannot be said for the UK, with few medical schools integrating longitudinal ultrasound education into the curriculum here . Furthermore, the use of HHU may lead to significant savings to the health system, when used appropriately …”
Section: The Why and The What For …mentioning
confidence: 98%
“…When used in carefully selected settings, telemedicine services can save costs over equivalent in‐person care 39–41 . Point‐of‐care diagnostics such as rapid diagnostic tests and point‐of‐care ultrasound may reduce facility cost through rapid delivery of results 42,43 . Learning strategies previously discussed, including MOOCs and Free Open Access Medicine (FOAMed), not only enable information to reach a broader audience and permit ongoing information sharing during a global pandemic but also result in reduced spending by learners 44,45 .…”
Section: Implications For Education and Training In Emmentioning
confidence: 99%
“…[39][40][41] Point-of-care diagnostics such as rapid diagnostic tests and point-of-care ultrasound may reduce facility cost through rapid delivery of results. 42,43 Learning strategies previously discussed, including MOOCs and Free Open Access Medicine (FOAMed), not only enable information to reach a broader audience and permit ongoing information sharing during a global pandemic but also result in reduced spending by learners. 44,45 Previously, access to critical appraisals of current medical literature was only available through expensive subscriptions, while now FOAMed resources like Journalfeed and Emergency Medicine Literature of Note allow individuals to access equally high-quality material for free.…”
Section: Research Innovations and Challengesmentioning
confidence: 99%